Pallidum and lateral ventricle volume enlargement in autism spectrum disorder - Turner, Andia H.; Greenspan, Kiefer S.; van Erp, Theo G.M. (Psychiatry research. Neuroimaging, 2016)
Studies on structural brain abnormalities in individuals with autism spectrum disorders (ASD) have been of limited size and many findings have not been replicated. In the largest ASD brain morphology study to date, we compared subcortical, total brain (TBV), and intracranial (ICV) volumes between 472 subjects with DSM-IV ASD diagnoses and 538 healthy volunteers (age range: 6–64 years), obtained from high-resolution structural brain scans provided by the Autism Brain Imaging Data Exchange (ABIDE). Compared to healthy volunteers, we found significantly larger pallidum (Cohen's d=0.15) and lateral ventricle volumes (Cohen's d=0.18) in ASD. These enlargements were independent of total brain volume and IQ, passed FDR correction for multiple comparisons, and were observed in overall, male-only, and medication-free subjects. In addition, intracranial, hippocampal, and caudate volumes were enlarged in ASD at a nominal statistical threshold of p<0.05. This study provides the first robust evidence for pallidum enlargement in ASD independent from TBV and encourages further study of the functional role of the pallidum in individuals with autism spectrum disorder. •This is the largest study of subcortical brain morphometry in ASD.•We found significant pallidum and lateral ventricle enlargement in ASD.•We also found evidence for ICV, hippocampal, and caudate enlargement in ASD.